Pengaruh Kualitas Pelayanan Terhadap Loyalitas Mahasiswa Pada Kampus Swasta (Studi kasus Pada Mahasiswa /I Stie Riau di Pekanbaru) - Sundari, Rina (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Nowadays with the development of technology the world of education is also growing, this is marked by the many emerging private universities / campus.Para private campus is competing to promote the campus to prospective students by prioritizing the quality. Starting from the facilities and infrastructure, the quality of lecturers, location, service and various other amenity.STIE Riau as one of the existing Private campus dipekanbaru already meet the criteria as a quality campus, this is evidenced by accreditation B currently. With this accreditation students are expected to be loyal to the campus and the quality of students who graduated can compete in the business world ini.Populasi in this study that is all students / I STIE Riau.Penelitian is done by using samples taken by simple Ramdom Sampling and analyzed using SEM WarpPLS. Primary data was obtained by distributing questionnaires to 90 students of STIE Riau and further analyzed by using SEM WarpPLS Keywords: Service Quality, Student Loyalty